2016
DOI: 10.1108/ijshe-05-2015-0091
|View full text |Cite
|
Sign up to set email alerts
|

Campus prosociality as a sustainability indicator

Abstract: Purpose Prosociality may in part determine sustainability behavior. Prior research indicates that pro-environmental behavior correlates with prosocial attitudes, and separately, that prosociality correlates with social support in homes and communities. Therefore, prosociality may constitute a keystone variable linking human well-being with pro-environmental behavior. The purpose of the paper is to test this conjecture. Design/methodology/approach Data from a multi-year student survey at the University of Mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 39 publications
3
16
0
Order By: Relevance
“…This finding suggests that cultural institutions may serve different functions in different contexts; whereas conservation beliefs seem to be unrelated to religious justifications in the United States, religion in Vanuatu may support conservation. This result is consistent with the proposal that religious beliefs are culturally transmitted because they solve adaptive problems (Henrich & Henrich, 2007; Norenzayan & Gervais, 2012) and is exemplary of the way solutions to issues of resource depletion can become integrated into cultural rules and institutions (Johannes, 2002; Turner & Berkes, 2006; Waring, Sullivan, & Stapp, 2016). Future research should continue to examine nuanced ways in which particular religious beliefs support or hinder conservation.…”
Section: Discussionsupporting
confidence: 86%
“…This finding suggests that cultural institutions may serve different functions in different contexts; whereas conservation beliefs seem to be unrelated to religious justifications in the United States, religion in Vanuatu may support conservation. This result is consistent with the proposal that religious beliefs are culturally transmitted because they solve adaptive problems (Henrich & Henrich, 2007; Norenzayan & Gervais, 2012) and is exemplary of the way solutions to issues of resource depletion can become integrated into cultural rules and institutions (Johannes, 2002; Turner & Berkes, 2006; Waring, Sullivan, & Stapp, 2016). Future research should continue to examine nuanced ways in which particular religious beliefs support or hinder conservation.…”
Section: Discussionsupporting
confidence: 86%
“…Most research on human cooperation in the last few decades has focused establishing the theoretical possibility of cooperation and altruism (Nowak, 2006), demonstrating that humans do, in fact, have prosocial and cooperative tendencies (Rand and Nowak, 2013), comparing human prosociality between cultures (Henrich et al, 2010(Henrich et al, , 2004, or with other species including ants and termites. Very little research has used human cooperation to understand organizational relationships and dynamics (but see Waring et al, 2016Waring et al, , 2014. Following the research on evolution of human cooperation (Henrich, 2015), we suggest that all organizations rely on cooperation of their constituents in some domains to some extent.…”
Section: Motivationmentioning
confidence: 83%
“…Cooperative behavior is the key for resolving these ‘social dilemmas’ where individually costly actions generate a better outcome for the collective group (see, for example, Ostrom 1990; Komorita and Parks, 1994; Weber et al , 2004; Poteete et al , 2010). Therefore, based on the binding trait of cooperation, pro-social and pro-environment behavior or attitudes are expected to be positively related and empirical evidence corroborates this conjecture (Kaiser and Byrka, 2011; Waring et al , 2016; Neaman et al , 2018). The term pro-social refers to an individual’s attitude or behavior that benefits other humans (Schroeder and Graziano, 2015), and pro-environment attitude or behavior is for the benefit of the environment, which implies that the beneficiaries include both humans and non-humans (Nolan and Schultz, 2015).…”
Section: Introductionmentioning
confidence: 86%
“…Social support refers to a socially conducive environment that an individual receives which is facilitated by members of the local community like family, friends, neighbors, university etc. Social support has been shown to enhance pro-social behavior (Waring et al , 2016; Guo, 2017) and social exclusion has been shown to hamper pro-social behavior (Twenge et al , 2007). Therefore, social support is expected to be positively associated with pro-social attitude or behavior, and pro-social attitude or behavior, in turn, is expected to be positively associated with a pro-environment attitude or behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation